PERLINDUNGAN HUKUM BAGI AHLI WARIS YANG TIDAK TERCANTUM DALAM AKTA KETERANGAN HAK WARIS YANG DIBUAT OLEH NOTARIS - Renaldo Putrokoesoemo; Mardi Candra; Felicitas Sri Marniati (Bajang Institute, 2026)
Inheritance occurs as a result of death. With the existence of a decedent, heirs and inherited property arise. A notary, as a public official, is authorized to draw up a Certificate of Inheritance Rights, which determines the heirs entitled to receive the inheritance and the respective portions they are entitled to. A phenomenon that occurs in society is the exclusion of an heir’s name from the Certificate of Inheritance Rights. The formulation of the problems in this research is as follows: (1) What is the legal responsibility of a Notary who prepares a Certificate of Inheritance Rights without including the name of one of the heirs? and (2) What legal protection is available for an heir whose name is not included in the Certificate of Inheritance Rights prepared by a Notary? The theories applied in this research are the Theory of Legal Responsibility according to Hans Kelsen and the Theory of Legal Protection according to Satjipto Rahardjo. The research method used is normative juridical research, namely legal research based on library materials or secondary data, consisting of primary, secondary, and tertiary legal materials. The research approaches employed include the statutory approach, case approach, analytical approach, and conceptual approach. The collection of legal materials is carried out by identifying and inventorying positive legal norms, book literature, journals, and other legal sources. The analysis of legal materials is conducted through legal interpretation, namely grammatical interpretation and systematic interpretation, as well as methods of legal construction, including analogical construction and legal refinement. The findings of this research indicate that the Notary’s responsibility depends on the presence or absence of fault in carrying out official duties. If the omission arises from the Notary’s lack of diligence in verifying heir data, the Notary may be held legally liable. However, if the deed is drawn up based on the statements of the appearing parties and the Notary has properly fulfilled all formal procedures, then the legal responsibility may not be imposed on the Notary. Legal protection for an heir whose name is not included may be pursued through civil legal remedies to affirm their rights, as well as through correction or annulment of the defective deed.